N and P Nutrition of Gmelina arbarea Roxb. Seedlings on Latosolic Soil. I: Effects of N and P Fertilizers and their Combinations on Growth and Physical Properties of Gmelina arbarea - Ogbonnaya, Chuks I (1992)
The effects of various doses of N and P fertilizers and their combinations on the growth and physical properties of Gmelina arborea Roxb. seedlings on latosolic soil were investigated. Four levels of N and P (0.0, 9.5, 19.0 and 28.5 g/plant corresponding to 0,1,2 and 3 levels, respectively) were applied in aU possible combinations. N was supplied as calcium amonium nitrate and P as super phosphate. Zero levels of Nand P (NOPO) were incorporated as the control. N and its combinations with P contributed significantly to improved wood specific gravity, plant height growth, radial growth (root collar' diameter), and dry matter production. Nand NP combinations were also the most effective in above-ground production (i.e. low root-shoot ratio) campal'ed to P alone and the control. Leaf area ratio (UR), howeuer, was reduced by most of the nutrient combinations cmnpared with the controL N1P3 produced the best wood specific gravity, N1P2 the most height growth, N3P1 the most radial growth and dry matter production, N3P2 the highest LAR, while the lowest root-shoot ratio or highest shoot production was obtained with N2PO and N3P1 nutrient combinations. Nutrient combinations involving N and P in the ratio oj3:1 (N3P1) are recommended for the growth of G. arborea seedlings on latosolic soil at the nursery or earl)1 establishment stage in the field.